A preparation method and application of UHPC tunnel jacking pipe
Through the preparation method of the new UHPC tunnel top tube, combined with oxide steel fibers and Fe3O4@SiO2 core-shell hydrophobic agent, the problem of insufficient mechanical properties and water-resistant permeability of concrete in the prior art is solved, and high strength and good anti-seepage effect are achieved.
Patent Information
- Application Number
- CN202410408277.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-07
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-04-07
AI Technical Summary
In the existing pipe top technology, the mechanical properties and water permeability of concrete are insufficient, making it difficult to meet the requirements of high strength and anti-seepage.
A new UHPC tunnel top tube is prepared by mixing cement, silicon fume, slag powder, fly ash, steel oxide fiber and Fe3O4@SiO2 core-shell hydrophobic agent in a specific proportion to form an efficient UHPC material, and the top tube is obtained by vibration assisted molding.
The excellent mechanical properties of UHPC (compressive strength and tensile strength) and water permeability resistance are achieved, extending the service life of steel fibers, and improving the compactness and uniformity of concrete.
Smart Images

Figure CN118184268B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultra-high performance concrete, and specifically relates to a preparation method of a novel UHPC tunnel jacking pipe and application thereof. Background Art
[0002] Pipe jacking is a construction method that uses mechanical thrust to push prefabricated pipe sections into the soil without large-scale excavation. This method is suitable for pipeline installation under obstacles such as railways, roads, rivers or buildings. Pipe jacking construction relies on the jacking force generated by the jacking equipment to overcome the friction between the pipeline and the surrounding soil and push the pipeline into the soil according to the designed slope. The key to pipe jacking construction lies in the adaptability issue. It is necessary to select appropriate pipe jacking methods and supporting equipment according to different geological conditions, construction conditions and design requirements. At present, pipe jacking technology is very mature and can cope with various complex underground engineering challenges. It is widely used in urban infrastructure, water conservancy projects, environmental protection and other fields, especially in urban areas. Because it has little impact on traffic and daily life, it has become an important construction method.
[0003] The pipe used in the pipe jacking technology is itself called a "pipe jacking". Pipe jacking is often used to transport liquids or in humid environments. Therefore, the concrete used to prepare the pipe jacking must not only meet certain strength requirements to ensure that it can withstand various stresses without damage during construction and use, but also needs to have excellent anti-seepage properties to prevent liquid penetration and cause corrosion of the internal steel bars. Summary of the invention
[0004] In order to solve the problems existing in the background technology, the present invention provides a novel UHPC tunnel jacking pipe preparation method and application thereof, which ensures that UHPC has excellent mechanical properties (compressive strength, tensile strength) and water penetration resistance.
[0005] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a novel method for preparing a UHPC tunnel jacking pipe, comprising the following steps:
[0006] S1. Mix 63 parts of cement, 7-10 parts of silica fume, 7-10 parts of slag powder, 12-15 parts of fly ash, 2.8-3 parts of steel oxide fiber, 1.8-2.2 parts of Fe3O4@SiO2 core-shell hydrophobic agent and 18-22 parts of quartz sand by weight to obtain a mixed dry material;
[0007] S2. By weight, first add 19-21 parts of water to the mixed dry material obtained in S1, and then gradually add 0.9-1.4 parts of high-efficiency water reducer and 0.4-0.6 parts of dispersant, mix well, and obtain UHPC material;
[0008] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe;
[0009] Wherein, the oxidized steel fiber is prepared by soaking the steel fiber in a sodium hypochlorite solution;
[0010] The Fe3O4@SiO2 core-shell hydrophobic agent is prepared by coating a SiO2 shell layer on the outside of Fe3O4 magnetic nanoparticles and then introducing a silane layer with an amino group on the surface.
[0011] Furthermore, the preparation method of the oxidized steel fiber is as follows:
[0012] A1. Prepare sodium hypochlorite solution with a concentration of 350-450 mg / L;
[0013] A2. Immerse the steel fiber in the sodium hypochlorite solution obtained in A1 for 10-20 minutes, take it out, rinse it with clean water, and dry it naturally to obtain oxidized steel fiber.
[0014] Furthermore, the diameter of the steel fiber is 0.1-0.2 mm, and the length of the steel fiber is 5-10 mm.
[0015] Furthermore, the preparation method of the Fe3O4@SiO2 core-shell hydrophobic agent is as follows:
[0016] B1, prepare a mixed solution of 320mL ethanol, 80mL water and 4mL ammonia, which is solution a;
[0017] B2. Take 9 mL of analytical pure hydrochloric acid and dilute it to 1 L with water to obtain a hydrochloric acid solution;
[0018] B3, take 3g of Fe3O4 magnetic nanoparticles, put them into the hydrochloric acid solution obtained in B2, ultrasonically disperse for 30min, filter, and rinse with deionized water three times to obtain acid-washed Fe3O4 particles;
[0019] B4, disperse the acid-washed Fe3O4 particles obtained in B3 in solution a obtained in B1, add 30 mL of tetraethoxysilane dropwise with stirring at room temperature, react for 8 h, filter, and vacuum dry at 65±2°C for 8 h to obtain Fe3O4@SiO2 core-shell material;
[0020] B5. Prepare a mixed solution of 400 mL of ethanol and 80 mL of water, which is solution b;
[0021] B6. Take 1 g of the Fe3O4@SiO2 core-shell material obtained in B4, put it into the solution b obtained in B5, and disperse it by ultrasonic. At room temperature, add 48 mL of 25% ammonia water and 40 mL of 3-aminopropyltriethoxysilane dropwise. Stir for 24 h, centrifuge, and vacuum dry to obtain the Fe3O4@SiO2 core-shell hydrophobic agent.
[0022] Furthermore, the particle size of the silica fume is less than 1 μm; the particle size of the slag powder is 10-30 μm; and the particle size of the fly ash is 1-60 μm.
[0023] Furthermore, the particle size of the quartz sand is 0.5-0.8 mm.
[0024] Furthermore, the cement is P.O52.5 grade cement.
[0025] Furthermore, the high-efficiency water reducer includes a polycarboxylate water reducer and an aminosulfonate water reducer, and the mass ratio of the two is 2-3:1.
[0026] Furthermore, the dispersant includes triisopropanolamine and / or triethanolamine.
[0027] In a second aspect, the present invention provides an application of a novel UHPC tunnel jacking pipe, wherein the novel UHPC tunnel jacking pipe is prepared by the above-mentioned preparation method, and the novel UHPC tunnel jacking pipe is used for laying municipal pipelines such as urban water supply, drainage, and gas, or for constructing tunnel structures such as subways and rail transit.
[0028] This application has the following beneficial effects:
[0029] 1. The addition of oxidized steel fiber can directly improve the mechanical properties (compressive strength and tensile strength) of concrete; the addition of Fe3O4@SiO2 core-shell hydrophobic agent can directly improve the water penetration resistance of concrete, effectively prevent the steel fiber from rusting when encountering water seepage, and thus extend the high-performance service life of the steel fiber; and the Fe3O4@SiO2 core-shell hydrophobic agent has excellent adsorption capacity, which can produce stronger adsorption capacity for oxidized steel fiber and silica fume and other components. This stronger adsorption effect helps to improve the density and uniformity of UHPC, thereby further improving the compressive strength and water penetration resistance of UHPC.
[0030] 2. The addition of steel fiber can improve the mechanical properties of concrete. For example, steel fiber can effectively withstand tensile stress, reduce the formation and expansion of cracks, and significantly improve the tensile strength of concrete.
[0031] In the preparation of oxidized steel fibers, the immersion treatment of the steel fibers in sodium hypochlorite solution can introduce oxygen-containing groups on the surface of the steel fibers. These oxygen-containing groups can enhance the chemical bonding and physical anchoring effect between the steel fibers and the concrete matrix, thereby enhancing the bonding force, thereby more effectively exerting the reinforcement effect of the steel fibers in the concrete and improving the compressive strength of the concrete.
[0032] 3. The addition of Fe3O4@SiO2 core-shell hydrophobic agent as a nanofiller can effectively fill the tiny pores inside the concrete, thereby reducing the penetration channels of water and harmful substances and reducing its permeability; in addition, the hydrophobic chemical bonds on the surface of Fe3O4@SiO2 core-shell hydrophobic agent can effectively resist the intrusion of water and improve the hydrophobic performance of the concrete surface;
[0033] In the preparation of Fe3O4@SiO2 core-shell hydrophobic agent, SiO2 coats Fe3O4 to form a core-shell structure, which can improve and regulate the properties of nanoparticles, enhance the stability and durability of nanoparticles, so that they can be better dispersed in concrete, and improve the overall density and uniformity; moreover, this core-shell structure can play a role in the interface area of concrete, by enhancing the density and bonding strength of the interface transition zone, thereby improving the overall waterproof performance;
[0034] The presence of 3-aminopropyltriethoxysilane will form a silane layer with amino groups on the surface of the nanoparticles. These amino groups can form more stable chemical bonds with the oxygen-containing groups on the surface of the oxidized steel fibers, thereby enhancing the adsorption between the two. On the one hand, the enhanced adsorption between components can promote the interaction between cement particles, making the structure tighter, thereby further improving the compressive strength of concrete. On the other hand, the enhanced adsorption between components helps to reduce the pores inside the concrete, thereby further reducing the water penetration resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The compressive strength comparison trend diagram of UHPC materials obtained in Examples 1-6 and Comparative Examples 1-9 of the present invention;
[0036] Figure 2 This is a comparative trend chart of the tensile strength of UHPC materials obtained in Examples 1-6 of the present invention and Comparative Examples 1-9;
[0037] Figure 3 The figure is a comparative trend chart of the water permeability resistance (90-day water permeability coefficient) of the UHPC materials prepared in Examples 1-6 of the present invention and Comparative Examples 1-9. DETAILED DESCRIPTION
[0038] The present application is further described in detail below with reference to the embodiments.
[0039] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available. Example 1
[0040] A novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0041] S1. Mix 63 parts of cement, 8 parts of silica fume, 9 parts of slag powder, 13 parts of fly ash, 2.9 parts of steel oxide fiber, 2 parts of Fe3O4@SiO2 core-shell hydrophobic agent and 20 parts of quartz sand by weight to obtain a mixed dry material;
[0042] S2. By weight, first add 20 parts of water to the mixed dry material obtained in S1, and then gradually add 1.2 parts of high-efficiency water reducer and 0.5 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0043] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe.
[0044] The oxidized steel fiber is prepared by soaking the steel fiber in a sodium hypochlorite solution. The specific preparation method of the oxidized steel fiber is as follows:
[0045] A1. Prepare a sodium hypochlorite aqueous solution with a concentration of 400 mg / L;
[0046] A2. Screen steel fibers with a diameter of 0.1-0.2 mm and a length of 5-10 mm, immerse them in the sodium hypochlorite solution obtained in A1 for 15 minutes, take them out, rinse them with clean water, and dry them naturally to obtain oxidized steel fibers.
[0047] The Fe3O4@SiO2 core-shell hydrophobic agent is prepared by coating a SiO2 shell layer on the Fe3O4 magnetic nanoparticles and then introducing a silane layer with an amino group on the surface. The specific preparation method of the Fe3O4@SiO2 core-shell hydrophobic agent is as follows:
[0048] B1, prepare a mixed solution of 320mL ethanol, 80mL water and 4mL ammonia, which is solution a;
[0049] B2. Take 9 mL of analytical pure hydrochloric acid and dilute it to 1 L with water to obtain a hydrochloric acid solution;
[0050] B3, take 3g of Fe3O4 magnetic nanoparticles, put them into the hydrochloric acid solution obtained in B2, ultrasonically disperse for 30min, filter, and rinse with deionized water three times to obtain acid-washed Fe3O4 particles;
[0051] B4, disperse the acid-washed Fe3O4 particles obtained in B3 in solution a obtained in B1, add 30 mL of tetraethoxysilane dropwise with stirring at room temperature, react for 8 h, filter, and vacuum dry at 65±2°C for 8 h to obtain Fe3O4@SiO2 core-shell material;
[0052] B5. Prepare a mixed solution of 400 mL of ethanol and 80 mL of water, which is solution b;
[0053] B6. Take 1 g of the Fe3O4@SiO2 core-shell material obtained in B4, put it into the solution b obtained in B5, and disperse it by ultrasonic. At room temperature, add 48 mL of 25% ammonia water and 40 mL of 3-aminopropyltriethoxysilane dropwise. Stir for 24 h, centrifuge, and vacuum dry to obtain the Fe3O4@SiO2 core-shell hydrophobic agent.
[0054] The particle size of silica fume is less than 1μm; the particle size of slag powder is 10-30μm; the particle size of fly ash is 1-60μm.
[0055] The particle size of quartz sand is 0.5-0.8mm.
[0056] The cement used is P.O52.5 grade cement.
[0057] The high-efficiency water reducer includes polycarboxylate water reducer and aminosulfonate water reducer, and the mass ratio of the two is 2.5:1.
[0058] The dispersant includes triisopropanolamine and triethanolamine, and the mass ratio of the two is 1:1.
[0059] The new UHPC tunnel jacking pipe prepared by the above preparation method is used for laying municipal pipelines such as urban water supply, drainage, gas, etc., or for building tunnel structures such as subways and rail transit. Example 2
[0060] The only difference between this embodiment and embodiment 1 is that in the preparation of the oxidized steel fiber, a sodium hypochlorite aqueous solution with a concentration of 350 mg / L is configured.
[0061] Specifically, the specific preparation method of oxidized steel fiber is as follows:
[0062] A1. Prepare a sodium hypochlorite aqueous solution with a concentration of 350 mg / L;
[0063] A2. Screen steel fibers with a diameter of 0.1-0.2 mm and a length of 5-10 mm, immerse them in the sodium hypochlorite solution obtained in A1 for 15 minutes, take them out, rinse them with clean water, and dry them naturally to obtain oxidized steel fibers. Example 3
[0064] The only difference between this embodiment and embodiment 1 is that in the preparation of the oxidized steel fiber, a sodium hypochlorite aqueous solution with a concentration of 450 mg / L is configured.
[0065] Specifically, the specific preparation method of oxidized steel fiber is as follows:
[0066] A1. Prepare a sodium hypochlorite aqueous solution with a concentration of 450 mg / L;
[0067] A2. Screen steel fibers with a diameter of 0.1-0.2 mm and a length of 5-10 mm, immerse them in the sodium hypochlorite solution obtained in A1 for 15 minutes, take them out, rinse them with clean water, and dry them naturally to obtain oxidized steel fibers. Example 4
[0068] The only difference between this embodiment and embodiment 1 is that the raw material component ratio of the UHPC material is different.
[0069] Specifically, a novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0070] S1. Mix 63 parts of cement, 7 parts of silica fume, 7 parts of slag powder, 12 parts of fly ash, 2.8 parts of steel oxide fiber, 1.8 parts of Fe3O4@SiO2 core-shell hydrophobic agent and 18 parts of quartz sand by weight to obtain a mixed dry material;
[0071] S2. By weight, first add 21 parts of water to the mixed dry material obtained in S1, and then gradually add 0.9 parts of high-efficiency water reducer and 0.4 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0072] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe. Example 5
[0073] The only difference between this embodiment and embodiment 1 is that the raw material component ratio of the UHPC material is different.
[0074] Specifically, a novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0075] S1. Mix 63 parts of cement, 10 parts of silica fume, 10 parts of slag powder, 15 parts of fly ash, 3 parts of steel oxide fiber, 2.2 parts of Fe3O4@SiO2 core-shell hydrophobic agent and 22 parts of quartz sand by weight to obtain a mixed dry material;
[0076] S2. By weight, first add 19 parts of water to the mixed dry material obtained in S1, and then gradually add 1.4 parts of high-efficiency water reducer and 0.6 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0077] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe. Example 6
[0078] The only difference between this embodiment and embodiment 1 is that the raw material component ratio of the UHPC material is different.
[0079] Specifically, a novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0080] S1. Mix 63 parts of cement, 7 parts of silica fume, 10 parts of slag powder, 12 parts of fly ash, 3 parts of steel oxide fiber, 2 parts of Fe3O4@SiO2 core-shell hydrophobic agent and 20 parts of quartz sand by weight to obtain a mixed dry material;
[0081] S2. By weight, first add 20 parts of water to the mixed dry material obtained in S1, and then gradually add 1 part of high-efficiency water reducer and 0.5 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0082] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe.
[0083] Comparative Example 1
[0084] The only difference between this comparative example and Example 5 is that in the preparation of oxidized steel fiber, the concentration of the sodium hypochlorite aqueous solution is 100 mg / L.
[0085] Specifically, the specific preparation method of oxidized steel fiber is as follows:
[0086] A1. Prepare a sodium hypochlorite aqueous solution with a concentration of 100 mg / L;
[0087] A2. Screen steel fibers with a diameter of 0.1-0.2 mm and a length of 5-10 mm, immerse them in the sodium hypochlorite solution obtained in A1 for 15 minutes, take them out, rinse them with clean water, and dry them naturally to obtain oxidized steel fibers.
[0088] Comparative Example 2
[0089] The only difference between this comparative example and Example 5 is that the oxidized steel fiber is replaced by steel fiber; that is, the steel fiber is not subjected to oxidation treatment.
[0090] Specifically, the steel fibers directly used in this comparative example are still selected to have a diameter of 0.1-0.2 mm and a length of 5-10 mm.
[0091] Comparative Example 3
[0092] The only difference between this comparative example and Example 5 is that the oxidized steel fiber is directly deleted from the raw material components.
[0093] Specifically, a novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0094] S1. Mix 63 parts of cement, 10 parts of silica fume, 10 parts of slag powder, 15 parts of fly ash, 2.2 parts of Fe3O4@SiO2 core-shell hydrophobic agent and 22 parts of quartz sand by weight to obtain a mixed dry material;
[0095] S2. By weight, first add 19 parts of water to the mixed dry material obtained in S1, and then gradually add 1.4 parts of high-efficiency water reducer and 0.6 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0096] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe.
[0097] Comparative Example 4
[0098] The only difference between this comparative example and Example 5 is that the Fe3O4@SiO2 core-shell hydrophobic agent is replaced by Fe3O4@SiO2 core-shell material, that is, during the preparation, the step of modifying the Fe3O4@SiO2 core-shell material with 3-aminopropyltriethoxysilane is deleted.
[0099] Specifically, the specific preparation method of Fe3O4@SiO2 core-shell material is as follows:
[0100] B1, prepare a mixed solution of 320mL ethanol, 80mL water and 4mL ammonia, which is solution a;
[0101] B2. Take 9 mL of analytical pure hydrochloric acid and dilute it to 1 L with water to obtain a hydrochloric acid solution;
[0102] B3, take 3g of Fe3O4 magnetic nanoparticles, put them into the hydrochloric acid solution obtained in B2, ultrasonically disperse for 30min, filter, and rinse with deionized water three times to obtain acid-washed Fe3O4 particles;
[0103] B4. Disperse the acid-washed Fe3O4 particles obtained in B3 in solution a obtained in B1, add 30 mL of tetraethoxysilane dropwise with stirring at room temperature, react for 8 h, filter, and vacuum dry at 65±2°C for 8 h to obtain Fe3O4@SiO2 core-shell material.
[0104] Comparative Example 5
[0105] The only difference between this comparative example and Example 5 is that the Fe3O4@SiO2 core-shell hydrophobic agent is replaced by a SiO2 hydrophobic agent, that is, the step of coating Fe3O4 with SiO2 is deleted during the preparation.
[0106] Specifically, the preparation method of the SiO2 hydrophobic agent is as follows:
[0107] B1, prepare a mixed solution of 400 mL ethanol and 80 mL water, which is solution b;
[0108] B2. Take 1g of nano-SiO2 and put it into the solution b obtained in B1, disperse it by ultrasonic, add 48mL of 25% ammonia water and 40mL of 3-aminopropyltriethoxysilane dropwise at room temperature, stir for 24h, centrifuge and vacuum dry to obtain the SiO2 hydrophobic agent.
[0109] Comparative Example 6
[0110] The only difference between this comparative example and Example 5 is that the Fe3O4@SiO2 core-shell hydrophobic agent is replaced by nano-SiO2.
[0111] Specifically, a novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0112] S1. Mix 63 parts of cement, 10 parts of silica fume, 10 parts of slag powder, 15 parts of fly ash, 3 parts of steel oxide fiber, 2.2 parts of nano-SiO2 and 22 parts of quartz sand by weight to obtain a mixed dry material;
[0113] S2. By weight, first add 19 parts of water to the mixed dry material obtained in S1, and then gradually add 1.4 parts of high-efficiency water reducer and 0.6 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0114] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe.
[0115] Comparative Example 7
[0116] The only difference between this comparative example and Example 5 is that the Fe3O4@SiO2 core-shell hydrophobic agent is replaced by Fe3O4 magnetic nanoparticles.
[0117] Specifically, a novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0118] S1. Mix 63 parts of cement, 10 parts of silica fume, 10 parts of slag powder, 15 parts of fly ash, 3 parts of steel oxide fiber, 2.2 parts of Fe3O4 magnetic nanoparticles and 22 parts of quartz sand by weight to obtain a mixed dry material;
[0119] S2. By weight, first add 19 parts of water to the mixed dry material obtained in S1, and then gradually add 1.4 parts of high-efficiency water reducer and 0.6 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0120] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe.
[0121] Comparative Example 8
[0122] The only difference between this comparative example and Example 5 is that the Fe3O4@SiO2 core-shell hydrophobic agent is directly deleted from the raw material components.
[0123] Specifically, a novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0124] S1. Mix 63 parts of cement, 10 parts of silica fume, 10 parts of slag powder, 15 parts of fly ash, 3 parts of steel oxide fiber and 22 parts of quartz sand by weight to obtain a mixed dry material;
[0125] S2. By weight, first add 19 parts of water to the mixed dry material obtained in S1, and then gradually add 1.4 parts of high-efficiency water reducer and 0.6 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0126] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe.
[0127] Comparative Example 9
[0128] The only difference between this comparative example and Example 5 is that the steel oxide fiber and the Fe3O4@SiO2 core-shell hydrophobic agent are directly deleted from the raw material components.
[0129] Specifically, a novel method for preparing a UHPC tunnel jacking pipe comprises the following steps:
[0130] S1. Mix 63 parts of cement, 10 parts of silica fume, 10 parts of slag powder, 15 parts of fly ash and 22 parts of quartz sand by weight to obtain a mixed dry material;
[0131] S2. By weight, first add 19 parts of water to the mixed dry material obtained in S1, and then gradually add 1.4 parts of high-efficiency water reducer and 0.6 parts of dispersant at the same time, mix well, and obtain UHPC material;
[0132] S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a new type of UHPC tunnel jacking pipe.
[0133] Test example
[0134] Test items and basis: 1. Compressive strength-GB / T50081-2019;
[0135] Tensile strength-GB / T50081-2019;
[0136] Water penetration resistance-GB / T50082-2009.
[0137] Test objects: UHPC materials were prepared according to Examples 1-6 and Comparative Examples 1-9.
[0138] Test results: See Table 1 and Appendix Figure 1-3 .
[0139] Table 1. Test data of the experimental example
[0140]
[0141] Result analysis: It can be seen from the data in Examples 1-6 and Table 1 that the UHPC material prepared by the present invention has stable performance and excellent mechanical properties (compressive strength, tensile strength) and water penetration resistance. Among them, Example 5 is the best example.
[0142] By combining the data in Table 1 and Figure 1 It can be seen that the addition of steel oxide fiber can improve the compressive strength of concrete; the addition of Fe3O4@SiO2 core-shell hydrophobic agent can also improve the compressive strength of concrete; and the effects of steel oxide fiber and Fe3O4@SiO2 core-shell hydrophobic agent on improving the compressive strength of concrete are synergistic, which can synergistically improve the compressive strength of concrete.
[0143] By combining the data in Table 1 and Figure 2 It can be seen that the addition of steel fiber can improve the tensile strength of concrete; the tensile strength of concrete can be further improved by oxidizing the steel fiber with sodium chlorate aqueous solution and then adding it to concrete; the addition of Fe3O4@SiO2 core-shell hydrophobic agent can also improve the tensile strength of concrete; and the oxidized steel fiber and Fe3O4@SiO2 core-shell hydrophobic agent work synergistically in improving the tensile strength of concrete.
[0144] By combining the data in Table 1 and Figure 3 It can be seen that the addition of steel oxide fiber can improve the water penetration resistance of concrete; the addition of Fe3O4@SiO2 core-shell hydrophobic agent can also improve the water penetration resistance of concrete; in the preparation of Fe3O4@SiO2 core-shell hydrophobic agent, SiO2 covers Fe3O4 to form a core-shell structure and 3-aminopropyltriethoxysilane participates in the modification, which are respectively beneficial to improving the water penetration resistance of concrete, and the two act synergistically; moreover, the effects of steel oxide fiber and Fe3O4@SiO2 core-shell hydrophobic agent on improving the water penetration resistance of concrete are synergistic, which can synergistically improve the water penetration resistance of concrete.
[0145] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0146] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a UHPC tunnel jacking pipe, characterized in that: The steps include: S1. Mix 63 parts of cement, 7-10 parts of silica fume, 7-10 parts of slag powder, 12-15 parts of fly ash, 2.8-3 parts of steel oxide fiber, 1.8-2.2 parts of Fe3O4@SiO2 core-shell hydrophobic agent and 18-22 parts of quartz sand by weight to obtain a mixed dry material; S2. By weight, first add 19-21 parts of water to the mixed dry material obtained in S1, and then gradually add 0.9-1.4 parts of high-efficiency water reducer and 0.4-0.6 parts of dispersant, mix well, and obtain UHPC material; S3, pouring the UHPC material obtained in S2 into a mold with a steel skeleton, performing vibration-assisted molding, curing, and demoulding to obtain a UHPC tunnel jacking pipe; Wherein, the oxidized steel fiber is prepared by soaking the steel fiber in a sodium hypochlorite solution; The preparation method of the oxidized steel fiber is as follows: A1. Prepare sodium hypochlorite solution with a concentration of 350-450 mg / L; A2, immerse the steel fiber in the sodium hypochlorite solution obtained in A1 for 10-20 minutes, take it out, rinse it with clean water, and dry it naturally to obtain oxidized steel fiber; The diameter of the steel fiber is 0.1-0.2 mm, and the length of the steel fiber is 5-10 mm; The Fe3O4@SiO2 core-shell hydrophobic agent is prepared by coating Fe3O4 magnetic nanoparticles with a SiO2 shell layer and then introducing a silane layer with an amino group on the surface; The preparation method of the Fe3O4@SiO2 core-shell hydrophobic agent is as follows: B1. Prepare a mixed solution of 320 mL of ethanol, 80 mL of water and 4 mL of ammonia, which is solution a; B2. Take 9 mL of analytical pure hydrochloric acid and dilute it to 1 L with water to obtain a hydrochloric acid solution; B3, take 3g of Fe3O4 magnetic nanoparticles, put them into the hydrochloric acid solution obtained in B2, ultrasonically disperse for 30min, filter, and rinse with deionized water three times to obtain acid-washed Fe3O4 particles; B4, disperse the acid-washed Fe3O4 particles obtained in B3 in solution a obtained in B1, add 30 mL of tetraethoxysilane dropwise with stirring at room temperature, react for 8 h, filter, and vacuum dry at 65±2°C for 8 h to obtain Fe3O4@SiO2 core-shell material; B5. Prepare a mixed solution of 400 mL of ethanol and 80 mL of water, which is solution b; B6. Take 1 g of the Fe3O4@SiO2 core-shell material obtained in B4, put it into the solution b obtained in B5, and disperse it by ultrasonic. At room temperature, add 48 mL of 25% ammonia water and 40 mL of 3-aminopropyltriethoxysilane dropwise. Stir for 24 h, centrifuge, and vacuum dry to obtain the Fe3O4@SiO2 core-shell hydrophobic agent.
2. The method for preparing a UHPC tunnel jacking pipe according to claim 1, characterized in that: The particle size of the silica fume is less than 1 μm; the particle size of the slag powder is 10-30 μm; and the particle size of the fly ash is 1-60 μm.
3. The method for preparing a UHPC tunnel jacking pipe according to claim 1, characterized in that: The particle size of the quartz sand is 0.5-0.8 mm.
4. The method for preparing a UHPC tunnel jacking pipe according to claim 1, characterized in that: The cement used is P.O52.5 grade cement.
5. The method for preparing a UHPC tunnel jacking pipe according to claim 1, characterized in that: The high-efficiency water reducer comprises a polycarboxylate water reducer and an aminosulfonate water reducer, and the mass ratio of the two is 2-3:
1.
6. The method for preparing a UHPC tunnel jacking pipe according to claim 1, characterized in that: The dispersant includes triisopropanolamine and / or triethanolamine.
7. An application of UHPC tunnel jacking pipe, characterized in that: The UHPC tunnel jacking pipe is prepared by the preparation method according to any one of claims 1 to 6. The UHPC tunnel jacking pipe is used for laying urban water supply, drainage, and gas municipal pipelines, or for constructing subway and rail transit tunnel structures.
Citation Information
Patent Citations
Rhodium monatomic magnetic catalyst as well as preparation method and application thereof
CN113145131A
Regenerated glass fiber reinforced plastic-polyvinyl alcohol hybrid fiber high-toughness concrete
CN114057450A
Ultra-high performance concrete and preparation method thereof
CN115304311A
Cited By
UHPC (Ultra High Performance Concrete) water drain pipe co-doped with defoaming agent and preparation method of UHPC water drain pipe
CN120864830A